Eficiencia de fungicidas para el control de Mycosphaerella fijiensis Morelet en Banano (Musa acuminata AAA) en la provincia de Los Ríos - Suarez García, Luis Adrián (2021)
The management of the disease known as Black Sigatoka in banana, caused by the ascomycete fungus Mycosphaerella fijiensis Morelet, is a real problem for the sustainable production of banana cultivation in Ecuador, since its control currently represents between 20% and 30% of production costs, due to the large amount of fungicides that must be used and the high number of application cycles required to control it, annually, with the consequent underlying environmental impacts. In order to establish economically viable and ecologically sustainable strategies for the management of the disease, it was proposed to study the use of several molecules with antifungal capacity against M. fijiensis and application frequencies in productive commercial banana plantations, and an experimental plantation to template level. Two experiments were established: A) The effect of two management strategies (treatments) of M. fijiensis was compared, based on the combination of systemic fungicides and protectants with different active ingredients, application frequencies, rotation and number of cycles per year. For this purpose, three plantations were selected that for several years used a strategy based on "lower load of fungicides" (Table 1), and three plantations based on a "greater load of fungicides" (Table 2), where for five years early infection was evaluated weekly in the fourth and fifth leaf, the total number of leaves in plants of three meters in height, zero weeks and eleven weeks. Additionally, the production costs generated with each strategy were analyzed. B) The effect of four groups of antifungal active ingredients (treatments) was studied, for which four rectangular plots of 720 m2 were established, within which 62 Williams variety banana plants were planted, to which the fungicides of according to the treatments. The percentage of leaf area affected (AFA%) by the disease, protection time / residuality (days) exerted by the antifungal active ingredients applied to the leaves from the moment of application, until the leaf ceases to be functional, was evaluated. number of photosynthetically active or functional leaves. The strategy based on a “lower load of fungicides” caused lower percentages of infection during the five years of evaluation. In the fourth sheet a reduction of 81.0%, 77.1%, 87.3%, 100, and 67.7% was found, while in the fifth sheet the reduction was 67.5%, 25.2%, 56.9%, 87.4%, and 19, 7%, for the years 2015, 2016, 2017, 2018, and 2019, respectively, compared to the percentages of infection generated by the strategy based on a “higher load of fungicides”. At the same time, the strategy based on a "lower fungicide load" generated higher values than the "higher fungicide load" strategy, with differences of 3.7%, 1.4%, 2.1%, 4.2%, and 4.5% for the number of leaves in plants of zero weeks of the years 2015, 2016, 2017, 2018, and 2019, while in plants of eleven weeks these differences occurred in the years 2015 and 2018, with 8.4%, and 6.3%, respectively. The reduction in production costs (USD ha-1 year) generated by the “lower fungicide load” strategy during the five years that the study lasted, was within the range of 25.7% (324.33 USD) to 42.8% (690.04 USD). On the other hand, the active ingredients of group 1 of fungicides (Epoxiconazole, Fenpropimorph, Metiram, Pyraclostrobin, Epoxiconazole, Boscalid, Diethofencarb) applied alone or in combinations during 12 cycles, generated the lowest percentages of AFA in the 12 application cycles, with AFA% ranges that were between 1.8 to 4.9 times, 1.3 to 5.1 times, and 4.4 to 11.1 times lower than those generated by groups 2, 3 and 4 (agricultural oil) of fungicides. These results show that there is no uniformity in the control capacity of each group of active ingredients, and that on the contrary it is common to detect this variability in the control of the disease.